Diurnal changes in photosynthesis of Antarctic fast ice algal communities determined by pulse amplitude modulation fluorometry - McMinn, A; Ryan, K; Gademann, R (Marine Biology, 2003)
The aim of this project was to determine both the diurnal changes in photosynthetic activity of Antarctic sea ice algae and also the protective mechanisms they use to mitigate the effects of in situ UV radiation. Changes in the diurnal photosynthetic parameters of fast ice algal communities at McMurdo Sound were measured in situ, using a custom designed monitoring pulse amplitude modulation fluorometer. The sea ice microalgae were able to adapt rapidly to either increasing or decreasing ambient irradiances. F/Fm' values were between 0.2 and 0.51, while Ek varied between 2.1 and 18 mol photons m-2 s-1. F/Fm', E k, and relative electron transfer rate (rETR) all varied sequentially over the course of a day. rETR and Ek were highest at midday at the highest irradiances, when there was apparent midday down regulation of photosynthesis, while F/Fm' was highest at midnight. The effects of natural UV radiation on sea ice were examined, but it was not possible to detect the effect of either UVB or UVA and UVB on photosynthesis. This was considered to be largely because of the large spatial and temporal heterogeneity of the under ice community, changing irradiances throughout the day and the relatively small change caused by UV.